Design, Optimization, and Characterization of Herbal Gel for Facial Application - Sharma, Pankaj (Asian Journal of Pharmaceutics (AJP), 2023)
The objective of this research is to create and test an herbal face gel for cosmetic uses that is comprised natural ingredients. A local market was the source of the amla (Emblica officinalis), masoor dal (Lens culinaris), and rose petals, which were then dried, powdered, geometrically mixed, and chemically evaluated as well as for organoleptic and physicochemical evaluation. Four separate mixtures, designated F1 to F4, were created using different ratios of components such E. officinalis, L. culinaris, rose petal powder, and polymers. All of the produced compositions were evaluated using a variety of metrics, including preformulation studies, pH, viscosity, spreadability, drying time, stability, statistical analysis, and an irritancy test. The viscosity of F1, F2, F3, and F4 was observed 15101.3 ± 0.55,149 44.9 ± 0.91, 16721.3 ± 0.90, and 16931.5 ± 0.96, respectively, and the pH was observed 5.4 ± 0.1, 5.6 ± 0.07, 5.5 ± 0.03, and 5.7 ± 0.1, respectively. The one-way analysis of variance approach demonstrated linearity for all answers at P ≤ 0.05.